Woman critiqued : translated essays on Japanese women's writing - Copeland, Rebecca L., 1956- (Honolulu : University of Hawai'i Press, 2006)
'Women Critiqued' offers English-language readers access to some of the salient critiques that have been directed at women writers, on the one hand, and reactions to these by women writers, on the other.
Frontmatter -- Contents -- Preface -- A Century Of Reading Women'S Writing In Japan. An Introduction / Copeland, Rebecca L -- Chapter 1: The Feminine Critique: ''Womanliness'' And Thewomanwriter / Copeland, Rebecca L. -- Chapter 2: The Essentialwomanwriter / Bardsley, Jan -- Chapter 3: The Narcissisticwomanwriter / Aoyama, Tomoko / Hartley, Barbara -- Chapter 4: The Resistingwomanwriter / Ericson, Joan E. -- Chapter 5:Womenwriters And Alternative Critiques / Seaman, Amanda -- Chapter 6:Women Critiquing Men:Watching The Ripples On The Pond / Copeland, Rebecca L. -- Glossary Of Names And Terms -- Bibliography -- Recommended Further Reading -- About The Contributors -- Index.
Includes bibliographical references (pages 253-271) and index.
Translated from the Japanese.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Japanese literature -- Women authors -- History and criticism; Japanese literature -- 20th century -- History and criticism; Women authors, Japanese -- 20th century; Japanese literature -- 1868- -- History and criticism; Écrits de femmes japonais -- Histoire et critique; Littérature japonaise -- 20e siècle -- Histoire et critique; Littérature japonaise -- 1868- -- Histoire et critique; Écrivaines japonaises -- 20e siècle.; LITERARY CRITICISM -- Asian -- General; LITERARY CRITICISM -- Asian -- Japanese; Japanese literature; Japanese literature -- Women authors; Women authors, Japanese; Literaturtheorie; Schriftstellerin; Japan; Japanisch; Since 1868; Criticism, interpretation, etc